2021
DOI: 10.3389/fncel.2021.624826
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Transcriptome Data Analysis Defines the Heterogeneity of Peripheral Nerve Cells in Homeostasis and Regeneration

Abstract: The advances in single-cell RNA sequencing technologies and the development of bioinformatics pipelines enable us to more accurately define the heterogeneity of cell types in a selected tissue. In this report, we re-analyzed recently published single-cell RNA sequencing data sets and provide a rationale to redefine the heterogeneity of cells in both intact and injured mouse peripheral nerves. Our analysis showed that, in both intact and injured peripheral nerves, cells could be functionally classified into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 71 publications
(226 reference statements)
0
73
0
Order By: Relevance
“…Next, we examined cell type specific expression of CD146 in both intact and injured mouse sciatic nerves with analyzed single cell RNA sequencing data GSE147285, which studied cell types and gene expression in intact mouse sciatic nerve and in the distal sciatic nerve at day 3 after sciatic nerve transection injury ( Toma et al, 2020 ; Chen et al, 2021 ), and GSE120678 which studied cell types and gene expression in the distal sciatic nerves at day 9 after sciatic nerve transection injury ( Carr et al, 2019 ; Chen et al, 2021 ). Single cell transcriptomics analysis demonstrated that CD146 is expressed in non-myelinating Schwann cells, vasculature-associated smooth muscle (VSM) cells and pericytes of intact mouse sciatic nerve ( Figure 2 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we examined cell type specific expression of CD146 in both intact and injured mouse sciatic nerves with analyzed single cell RNA sequencing data GSE147285, which studied cell types and gene expression in intact mouse sciatic nerve and in the distal sciatic nerve at day 3 after sciatic nerve transection injury ( Toma et al, 2020 ; Chen et al, 2021 ), and GSE120678 which studied cell types and gene expression in the distal sciatic nerves at day 9 after sciatic nerve transection injury ( Carr et al, 2019 ; Chen et al, 2021 ). Single cell transcriptomics analysis demonstrated that CD146 is expressed in non-myelinating Schwann cells, vasculature-associated smooth muscle (VSM) cells and pericytes of intact mouse sciatic nerve ( Figure 2 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…*p-value < 0.05. Toma et al, 2020;Chen et al, 2021). Previously, we studied gene expression changes in both DRG and the distal nerve stump in the rat by microarray analysis, and identified CD146 as one of DEGs in the distal nerve stump (Yi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latent phase lasts up to 36 h wherein the axons appear normal and for much of this time retain the ability to conduct an action potential, although the axon becomes committed to degenerate ( Tsao et al, 1999 ; Beirowski et al, 2004 ; Beirowski et al, 2005 ; Conforti et al, 2014 ). This is also the stage in which the immune system is first seen to be involved; tissue-resident macrophages are activated and bone-marrow derived macrophages, neutrophils and phagocytes infiltrate into the nerve ( Perkins and Tracey, 2000 ; Sta et al, 2014 ; Zigmond and Echevarria, 2019 ; Boissonnas et al, 2020 ; Ydens et al, 2020 ; Chen et al, 2021 ). There is also an injury-associated increase in the levels of cytokines ( Yi et al, 2017 ).…”
Section: Axon Degeneration Research From 1850 To Todaymentioning
confidence: 99%